The perpetration of antisocial behaviours in young cape verdean: a predictive study - Dias, Jorge; Formiga, Nilton; Gonçalves, Rui Abrunhosa; Cunha, Olga; Conde, Rita (Actualidades en Psicología, 2017)
In Cape Verde, since the end of the 1990s years there has been a significant increase of antisocial behaviors committed by young people (aged 12 and 21). Nevertheless, knowledge of factors that lie at the origin and maintenance of such behaviors still reveals incident or are still at an early stage. In this study, we tried to identify possible risk factors that forecast antisocial behaviour, self-reported by using, for this purpose, the International Self-Report Delinquency Study (ISRD-3).The sample consisted of 535 students from both sexes attending public secondary education in Cape Verde, of which 284 (53%) were females and 247 (46.25%) males. The age of young people varies between 13 and 21 years, having an average age of 16.66 and a standard deviation of 2.04. The results indicate that sex is a strong predictor of perpetration of antisocial behaviors, given that males show greater probability of engaging in antisocial behaviors. Teenagers with less antisocial attitudes are also those with less probability to engage in antisocial behaviors. Likewise, and even if only reveals marginally significant, adolescents who report major involvement in antisocial activities highlights a greater probability to engage in disruptive hobby activities. These results are analyzed in terms of their implications forthe prevention of delinquency.